1997
DOI: 10.1088/0268-1242/12/10/019
|View full text |Cite
|
Sign up to set email alerts
|

The fabrication and characterization of nickel oxide films and their application as contacts to polymer/porous silicon electroluminescent devices

Abstract: Porous silicon electroluminescent devices have been fabricated from n-type substrates using indium tin oxide, hole-transporting poly(9-vinyl carbazole) and p-type nickel oxide films as hole injecting contacts. The addition of the polymer layer, which increases the contact area by penetrating into the porous microstructure, leads to an increase in the device quantum efficiency of two orders of magnitude. The replacement of indium tin oxide by nickel oxide, formed by a thermal evaporation process, lowers the dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…[12,13] The low thickness of the oxide layer, for example, also alters the resistivity value, increasing it, according to the Fuchs-Sondheimer law. [14,15] It is then concluded that it is difficult to know with exactness the thickness and electrical resistivity of the oxide layers. Fortunately, the aforementioned effects do not generally alter more than two orders of magnitude the resistivity value of the bulk oxides, which can be found tabulated.…”
Section: Resultsmentioning
confidence: 99%
“…[12,13] The low thickness of the oxide layer, for example, also alters the resistivity value, increasing it, according to the Fuchs-Sondheimer law. [14,15] It is then concluded that it is difficult to know with exactness the thickness and electrical resistivity of the oxide layers. Fortunately, the aforementioned effects do not generally alter more than two orders of magnitude the resistivity value of the bulk oxides, which can be found tabulated.…”
Section: Resultsmentioning
confidence: 99%
“…The electrical resistivity of the NiO, according to the literature [19][20][21], is defined in the range of 0.14×10 7 to 60×10 7 nΩ×m in Model I, and kept as 0.3×10 7 nΩ×m for Model II if not specified. The incertitude of the electrical resistivity of oxide film is discussed in the last part of section IV.…”
Section: Finite Element (Fe) Modelingmentioning
confidence: 99%
“…Due to the electrical interaction between nano-spots, the electrical resistance increases when the spots are closer, and the difference between FEM and analytical model becomes bigger. 3) The influence of electrical resistivity of oxide film The electrical resistivity of nickel oxide film is defined as 3×10 6 nΩ×m in previous sections, which is chosen based on the values in the literature: (0.14-60)×10 7 (nΩ×m) [19][20][21]. These values were measured with samples fabricated in controlled conditions, either thermal evaporation or sputtering, and might be different from the natural formed oxide film.…”
Section: ) Multiple Nano-spotsmentioning
confidence: 99%
“…Another sources of uncertainty are the crystalline or amorphous nature of the oxide layers, the number of vacancies and impurities in the oxide and any other factor altering the conductivity [8,9]. Thus, the nanometric thickness of the oxides diminishes the resistivity according to the Fuchs-Sondheimer law [10,11]. Fortunately, despite the aforementioned effects, the conductivity of the oxide layer does not differ in more than one order of magnitude with respect to the conductivity of the bulk oxide, which can be found in the literature.…”
Section: Introductionmentioning
confidence: 99%